(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Education, a cornerstone of societal development, has undergone significant transformations over the past few decades. The rapid advancement of technology shifts in pedagogical approaches, and the increasing emphasis on inclusivity and lifelong learning are reshaping the educational landscape. This article explores the current state of education, the challenges it faces, and the innovative solutions that are emerging to address these issues.